Analisis Faktor-faktor yang Mempengaruhi Capaian Hasil Pembelajaran Pelatihan Jarak Jauh Bea Dan Cukai di Masa Pandemi Covid-19 (Studi Balai Diklat Keuangan Makassar) - Azwar Azwar (Fakultas Ilmu Pendidikan-Universitas Negeri Malang, 2022)
This study aims to measure the success of the implementation of distance learning systems in the field of Customs and Excise in the Financial Education and Training Agency of Makassar during the pandemic by analyzing the factors that affect the achievement of learning outcomes. This study used data obtained from respondents through questionnaires and quantitative approaches through component or variant-based of Structural Equation Modelling (SEM) techniques with Partial Least Square (PLS). The results showed that in general the distance learning system organized has not fully run well and successfully based on indicators or approach of DeLone and McLean model. Based on the four proposed hypotheses, it is not entirely proven and acceptable. The system quality affects user satisfaction and user satisfaction also affects the net benefits. Meanwhile, the information quality and service quality has no effect on user satisfaction. Financial Education and Training Agency of Makassar as a technical implementer of BPPK in the region is expected to improve the quality of information and quality of services in order to improve the satisfaction of training participants that will have an impact on the achievement of learning outcomes.